2019
DOI: 10.1177/1469066719879297
|View full text |Cite
|
Sign up to set email alerts
|

Development of simultaneous determination of empagliflozin and metformin in human plasma using liquid chromatography–mass spectrometry and application to pharmacokinetics

Abstract: A rapid and sensitive liquid chromatography–mass spectrometry method was developed, optimized, and validated for simultaneous quantification of empagliflozin and metformin in human plasma using empagliflozin D4and metformin D6 as an internal standard. Analytes and internal standard were extracted from plasma by optimized solid-phase extraction technique using Strata X polymeric reverse phase (30 mg-1cc) solid-phase extraction cartridges. The prepared samples were chromatographed on Orosil C18 column (150 × 4.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Following a thorough study of the literature, several methods for analyzing MET alone in various samples (plasma, urine, liver, brain, kidney, and muscles) were reported, including HPLC [14][15][16][17][18][19], HILIC [20], LC/MS/MS [21][22][23][24], HILIC/MS [25], and GC/MS [26]. MET in conjunction with various medications in various plasma samples was also estimated by HPLC [27][28][29][30][31][32], LC/MS/MS [33][34][35][36][37][38][39][40], and HILIC/MS [41,42] methods.…”
Section: Introductionmentioning
confidence: 99%
“…Following a thorough study of the literature, several methods for analyzing MET alone in various samples (plasma, urine, liver, brain, kidney, and muscles) were reported, including HPLC [14][15][16][17][18][19], HILIC [20], LC/MS/MS [21][22][23][24], HILIC/MS [25], and GC/MS [26]. MET in conjunction with various medications in various plasma samples was also estimated by HPLC [27][28][29][30][31][32], LC/MS/MS [33][34][35][36][37][38][39][40], and HILIC/MS [41,42] methods.…”
Section: Introductionmentioning
confidence: 99%
“…Many chromatographic methods with UV and mass detection were reported for the assay of EFN in pharmaceutical dosage form and biological fluids either alone or in combination with linagliptin, metformin, and/or other antidiabetics [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Yet, they lack of being simple, fast, and cost-effective approaches due to the required costly complex instrumentation and time-consuming multipart analytical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature review it was found that, many analytical techniques have been reported for the determination of EMP and LIN, including UV spectrophotometry (Amrutiya et al, 2017;Ayoub, 2016;Cholke et al, 2019;Padmaja & Veerabhadram, 2015), voltammetry (Naccar, Saleh, Omar, Haredy, & Derayea, 2020), HPTLC (Bhole, Wankhede, & Pandey, 2017;Thakor, Amrutkar, & Chaudhari, 2019), HPLC (Abdel-Ghany, Ayad, & Tadros, 2018Al-Sabti & Harbali, 2020;Attimarad, Nagaraja, Aldhubaib, Nair, & Venugopala, 2014;Basak, Gouru, Bera, & Nagappan, 2019;Donepudi & Achanta, 2018;El-Bagary, Elkady, & Ayoub, 2013;Ganorkar, Askarkar, Gupta, & Milind, 2020;Geetha Swarupa, Lakshmana Rao, Prasad, & Suresh Babu, 2016;Gholami, Bahrami, & Faraji, 2020;Manoel et al, 2020;Naazneen & Sridevi, 2016;Padmaja & Veerabhadram, 2017;Rajbangshi, Alam, Hossain, Islam, & Rouf, 2018;Salapaka et al, 2019;Sharif et al, 2020;Supriya Reddy, Chandan, Sai Charan, & Akshay, 2020;Vemula, Dodda, Balekari, Panga, & Veeresham, 2015;Wattamwar, Mungantiwar, Halde, & Pandita, 2020;Yadav, Dornala, Swain, Prabha, & Samanthula, 2020), UPLC (Ayoub, 2015;Dubey, Singh, Tyagi, Bhardwaj, & Raghav, 2014;Jagadabi, Kumar, Pamidi, Ramaprasad, & Nagaraju, 2018;Madana Gopal & Sridhar, 2017;Nannapaneni, Jalalpure, Muppavarapu, & Sirigiri, 2016)…”
Section: Introductionmentioning
confidence: 99%